The illusion of accountability in the European Union - Karlsson, Christer; Persson, Thomas; Gustavsson, Sverker (Taylor & Francis, 2009)
This book examines accountability in the EU from different perspectives and considers whether EU citizens have real opportunities for holding decision-makers accountable. This book critically analyses five arguments which claim there are sufficient means for holding decision-makers to account in the Union.